MAINTENANCE AND INSTRUCTIONS FOR VIRTUAL REALITY SYSTEM ASSEMBLIES - Lara, Miguel Beteta; de Oliveira, Victor Inacio; Yamamoto, Rogerio Issamu; da Silva, Marcones Cleber Brito; de Oliveira, Anderson Alves; Janes, Ricardo; Pirola, Peterson Carlos (Seven Editora, 2025)
The main objective of this work is to create an integrated environment in virtual reality for simulation of maintenance processes, prototyping and assembly of customized industrial automation sets. For this, an application was developed using the UNITY software. The model was tested and simulated for various types of assemblies, using elements such as pneumatic cylinders, compressed air handling units and process automation valves. The results show that it is possible to create a new way to teach workers and students to adapt to these machinery and equipment, concluding a way to optimize future learning and instruction processes to facilitate the maintenance of components of a company and didactics of new members in the world of industrial automation, in addition to contributing to the advancement of technology and development of industry 4.0. DOI: https://doi.org/10.56238/sevened2024.037-129